Contribuciones al estudio de la teoría de la empatía de Husserl en textos póstumos - Savignano, Alan Patricio (2019)
“Contributions to the Study of Husserl’s Empathy Theory in his Posthumous Texts”. This is a study about the development of Edmund Husserl’s empathy theory. It seeks to reconstruct two of the main milestones regarding the reflections on empathy as an intentional apprehensive experience of an alien subjectivity, from an interpretation of posthumous texts on intersubjectivity edited by Iso Kern in 1973 in volumes XIII, XIV and XV of Husserliana. The first milestone is the discussion from the early 1900s Husserl engages with, on the one hand, in relation to the theory of inference by analogy of Benno Erdmann - originally formulated by John Sturart Mill - and, on the other hand, in relation to the theory of empathy as an instinct of imitation and expression of Theodor Lipps. The second is the reworking of the concept of empathy based on genetic phenomenology and the discovery of passive synthesis based on the cogitative acts of the ego. I maintain in this work that these two milestones of Husserlian thought regarding intersubjectivity are not completely unlinked: the notions of analogy and non-yoician operations, so important in the second period, were already present in their own way in the critical interpretation of theories from Erdmann/Mill and Lipps.